Asymmetric Total Synthesis of Heronamides A–C: Stereochemical Confirmation and Impact of Long‐Range Stereochemical Communication on the Biological Activity. Issue 25 (12th May 2016) - Kanoh, Naoki; Itoh, Shunya; Fujita, Kohei; Sakanishi, Kohei; Sugiyama, Ryosuke; Terajima, Yuta; Iwabuchi, Yoshiharu; Nishimura, Shinichi; Kakeya, Hideaki
Abstract: Heronamides are biosynthetically related metabolites isolated from marine‐derived actinomycetes. Heronamide C shows potent antifungal activity by targeting membrane phospholipids possessing saturated hydrocarbon chains with as‐yet‐unrevealed modes of action. In spite of their curious hypothesized biosynthesis and fascinating biological activities, there have been conflicts in regard to the reported stereochemistries of heronamides. Here, we describe the asymmetric total synthesis of the originally proposed and revised structures of heronamide C, which unambiguously confirmed the chemical structure of this molecule. We also demonstrated nonenzymatic synthesis of heronamides A and B from heronamide C, which not only proved the postulated biosynthesis, but also confirmed the correct structures of heronamides A and B. Investigation of the structure–activity relationship of synthetic and natural heronamides revealed the importance of both long‐range stereochemical communication and the 20‐membered macrolactam ring for the biological activity of these compounds. Abstract : Long‐distance communication matters : Asymmetric total synthesis of the originally proposed and revised structures of heronamide C, and nonenzymatic synthesis of heronamides A and B from heronamide C is described (see scheme). Investigation of the structure–activity relationship of synthetic and natural heronamides revealed the importance of both long‐range stereochemical communication and the 20‐membered macrolactam ring for the biological activity of these compounds.